Mapped patterns in sediment samples of modern pollen from southeastern Canada and northeastern United States - Webb, Thompson; Yeracaris, G.; Richard, Pierre (Géographie physique et Quaternaire)

(untitled) (Les Presses de l’Université de Montréal, 1978)
Isopoll maps based on 173 modern-pollen samples illustrate the geographical patterns of 12 pollen types within a 600,000 sq. km area centered in southern Québec. The mapped patterns reflect several scales of vegetational pattern that ranges from the major regional change between conifer-hardwood forest and boreal forest down to the minor local differences in vegetation between nearby sites. Picea and other arboreal pollen types are most representative of the regional patterns, whereas Cyperaceae and Ericaceae pollen often vary markedly between adjacent sites. Further analysis of these pollen data explored how much differences in sediment type and variations in analyst practices among the samples can affect the sensitivity of the pollen data to certain of the vegetational patterns. The set of 173 samples was divided into three subsets, two of which differ in sediment types and two of which differ in analyst practices. The distributions of pollen types are then correlated between the contrasting subsets, and their principal components are compared. These results show that only small differences exist among the subsets in their portrayal of the major vegetational patterns, but marked differences appear in the record of certain minor patterns.